Memorandum of Understanding between the International Livestock Research Institute (ILRI) and AmboUniversity - International Livestock Research Institute; Ambo University (2021)
Memorandum of understanding (MOU) between the International Livestock Research Institute (ILRI) and Ambo University. MOU signed on December 23, 2021, by Jimmy Smith, Director-General of ILRI and Bayissa Leta, Vice-President of Ambo University.